Sitio in the city infill development in residual spaces as resettlement - Villanueva, Mac Andrew
Shelter has always been the center of the problem of many marginalized families in urban centers. People from rural and suburban regions migrate to the city to find better economic opportunities and basic services. However, there is perceived scarcity of land and monopoly of those who can pay for property. These urban poor families do not simply provide for themselves but they also serve as the backbones of social reproduction in cities. They offer a significant hand in the labor force which ensues economic progress. However without proper homes, they are forced to flee the city and settle in far flung areas which defeats the purpose of their initial migration. One primary example is the Sitio San Roque community who has been in Barangay Pag-asa, Quezon City for the longest time. Now, they face endless demolitions from the local government agencies and private developers who plan to develop the land into a Central Business District. With these facts at hand, this study aims to provide an alternative yet accessible way of providing a nurturing and productive home to these families. The symbiosis between informal work and the city should not only be enriched, but also made fair for the oppressed. Residual spaces, on the other hand, are urban voids that are left unused and abandoned. Most common examples are silvers spaces in between buildings, areas under infrastructure, and easements. However, the essence of residual spaces is characterized by the lack of a vital function, left untouched by human activity and often severing a space from another. These areas can be revitalized by bringing in communities that thrive in human interaction and public presence. And these qualities can be largely attributed to informal work. In doing so, these once dead areas would be renewed, the importance of the urban poor sectors would be highlighted, and they will have their own home right where they make a better life for themselves.